2002
DOI: 10.1037/0022-0663.94.3.638
|View full text |Cite
|
Sign up to set email alerts
|

Revision of achievement goal theory: Necessary and illuminating.

Abstract: C. Midgley et al. (2001) raised important questions about the effects of performance-approach goals. The present authors disagree with their characterization of the research findings and implications for theory. They discuss 3 reasons to revise goal theory: (a) the importance of separating approach from avoidance strivings, (b) the positive potential of performance-approach goals, and (c) identification of the ways performance-approach goals can combine with mastery goals to promote optimal motivation. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

81
745
12
75

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 956 publications
(913 citation statements)
references
References 48 publications
81
745
12
75
Order By: Relevance
“…Individuals higher in achievement motivation are more likely than those lower in achievement motivation to endorse all achievement goals: mastery, performance-approach, and performance-avoidance goals (Elliot & McGregor, 2001). Thus, if the presence of competence-related stereotypes leads to the adoption primarily of performanceavoidance goals at the expense of other achievement goals, then the functions that the other kinds of goals typically serve for individuals higher in achievement motivation will not be served (e.g., Harackiewicz et al, 2002;Linnenbrink, 2005;Pintrich, 2000;Wolters, 2004).…”
Section: Role Of Achievement Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals higher in achievement motivation are more likely than those lower in achievement motivation to endorse all achievement goals: mastery, performance-approach, and performance-avoidance goals (Elliot & McGregor, 2001). Thus, if the presence of competence-related stereotypes leads to the adoption primarily of performanceavoidance goals at the expense of other achievement goals, then the functions that the other kinds of goals typically serve for individuals higher in achievement motivation will not be served (e.g., Harackiewicz et al, 2002;Linnenbrink, 2005;Pintrich, 2000;Wolters, 2004).…”
Section: Role Of Achievement Motivationmentioning
confidence: 99%
“…In contrast, effects of performance-approach goals on performance and motivation appear to depend both on the context and on individual differences. A performance-approach goal is defined as wanting to demonstrate competence in comparison to others (e.g., Elliot & Church, 1997;e.g., I want to do the best on the computer science task) and often is associated with positive effects on learning in the college classroom (e.g., Harackiewicz et al, 2002). These goals have also been associated with positive, null, or negative effects on interest, depending on other individual or contextual factors (e.g., Elliot & McGregor, 2001;Harackiewicz & Elliot, 1993;Wolters, 2004;cf.…”
Section: The Step Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The additive goal pattern suggests that both mastery and performance-approach goals have independent positive main effects on a given outcome (e.g., exam grade). In the specialized pattern, mastery and performance-approach goals affect different outcomes (for instance, interest and performance, respectively; for a review, see Harackiewicz, Barron, Pintrich, Elliot, & Thrash, 2002). In the selective goal pattern, individuals could actually switch from one type of goals to the other depending on the situation requirement.…”
Section: The Multiple-goal Approachmentioning
confidence: 99%
“…To date, evidence has shown that avoidance goals (masteryavoidance or performance-avoidance goals) are associated with maladaptive outcomes such as anxiety, disorganised study habits, fear of failure, self-handicapping, and low achievement or task interest (Elliot & McGregor, 2001;Senko, Hulleman, & Harackiewicz, 2011;Senko & Miles, 2007). In contrast, approach goals are associated with adaptive outcomes such as intrinsic motivation, interest, and use of deep learning strategies (Harackiewicz et al, 2002;Harackiewicz et al, 2008). Moreover, there is evidence that the two approach goals predict different outcomes.…”
Section: Introductionmentioning
confidence: 99%